Activity of selenium on cell proliferation, cytotoxicity, and apoptosis and on the expression of CASP9, BCL-XL and APC in intestinal adenocarcinoma cells - Mauro, M. O. [UNESP]; Sartori, Daniele; Oliveira, Rodrigo Juliano; Ishii, Priscila Lumi [UNESP]; Mantovani, Mario Sergio; Ribeiro, Lucia Regina [UNESP] (Elsevier B.V., 2011)
Intestinal cancers are correlated with diet. Thus, determining and understanding nutrient-genome interactions is important. The present work assessed the action of the oligoelement selenium on cell proliferation, cytotoxicity, and in situ apoptosis induction and on the expression CASP9, BCL-XL and APC genes in intestinal adenocarcinoma cells (HT29). HT29 cells were cultured and treated with selenium at concentrations of 5, 50 and 500 ng/mL with or without the damage-inducing agent doxorubicin. These cells were then evaluated for cytotoxicity (MTT), cell proliferation and in situ apoptosis induction. To evaluate gene expression, only the cells treated with 500 ng/mL of selenium were used. RNA was extracted from these cells, and the expressions of CASP9, BCL-XL and APC were analyzed by the RT-PCR method. The GAPDH gene was used as a reference gene. The MTT assay showed that selenium was not cytotoxic at any of the concentrations tested. The cell proliferation assay showed that selenium did not interfere with cell proliferation at the three concentrations tested. In contrast, when the three concentrations were combined with doxorubicin, a significant decrease in the proliferation rate was observed. The apoptosis rate was significantly increased in the selenium (500 ng/mL) and doxorubicin group. CASP9 expression was increased and BCL-XL expression decreased in the selenium (500 ng/mL) and doxorubicin group. APC was significantly increased in the selenium group alone. These results show that selenium increases apoptosis, especially when it is associated with a damage-inducing agent. Also, selenium has an important role in the expression of the APC gene, which is related to cell cycle regulation. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Selenium; Oligoelement; Gene expression; RNA